2017
DOI: 10.1177/1362361316687989
|View full text |Cite
|
Sign up to set email alerts
|

‘The dots just don’t join up’: Understanding the support needs of families of children on the autism spectrum

Abstract: Much research has documented the elevated levels of stress experienced by families of autistic children. Yet remarkably little research has examined the types of support that these families perceive to be beneficial to their lives. This study, co-produced by researchers and school-based professionals, sought to establish these families' support needs from their own perspectives. In total, 139 parents of autistic children with additional intellectual disabilities and limited spoken communication, all attending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 88 publications
5
61
1
6
Order By: Relevance
“…In particular, parents in this study described being excluded because of insufficient care modalities not addressing medical and behavioural manifestations associated with the rare NDD. This is congruent with finite studies on parents' experiences with rare diseases (Galpin et al, 2017;Pelentsov, Laws, & Esterman, 2015). Compartmentalized care models within health and government supports are designed for periodic health incidents, not for complex disease trajectories such as complex rare NDDs (Grut & Kvam, 2013;von der Lippe, Diesen, and Feragen (2017).…”
Section: Discussionsupporting
confidence: 59%
“…In particular, parents in this study described being excluded because of insufficient care modalities not addressing medical and behavioural manifestations associated with the rare NDD. This is congruent with finite studies on parents' experiences with rare diseases (Galpin et al, 2017;Pelentsov, Laws, & Esterman, 2015). Compartmentalized care models within health and government supports are designed for periodic health incidents, not for complex disease trajectories such as complex rare NDDs (Grut & Kvam, 2013;von der Lippe, Diesen, and Feragen (2017).…”
Section: Discussionsupporting
confidence: 59%
“…Parents must become expert care providers addressing pervasive health and social needs, navigating fragmented discoordinated care within health‐care and government support systems, while carrying a heavy burden of care . Within the finite studies of parent experiences in caring for children with medical complexity, parents describe carrying significant emotional and social responsibility when caring for their children because of overwhelming circumstances and struggles . Parents express being stressed, overwhelmed and overextended with providing care at home where similar care within hospital settings required highly specialized providers …”
Section: Introductionmentioning
confidence: 99%
“…Previous research has highlighted the negative impact that eating difficulties can have on pupils within the educational setting (Koenig and Rudney, 2010). In line with previous studies that have shown a strong correlation between mealtime behavior and parental stress and a negative impact on family life (Kerwin et al, 2005;Bagby et al, 2012;Suarez et al, 2014a;Postorino et al, 2015;Thullen and Bonsall, 2017), parents have themselves identified their child's diet as a priority area for support (Galpin et al, 2017). The aim of the current study was, therefore, to examine the impact of a sensory based intervention to address food selectivity in autistic pupils that could be delivered in a school setting by teaching staff.…”
Section: Aimmentioning
confidence: 52%
“…This study sought to address food selectivity in autistic children through a sensory based intervention delivered in school by existing school staff. The study is unique in that it sought to translate previously clinically based types of sensory feeding interventions into a viable part of the daily school routine (examining the effectiveness of the intervention) that would address a difficulty that had been identified as a priority area for support by parents (Galpin et al, 2017). A further contribution to the wider literature is, therefore, to respond to the call for autism research to address issues identified as priorities by the autism community (Pellicano et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation